Efektivitas Pembelajaran menggunakan Learning Management System Berbasis Moodle - Michel Viaren; Taali Taali (Jurnal Pendidikan Teknik Elektro, 2022)
This research was conducted with the aim of looking at the effectiveness of learning using a moodle-based Learning Management System (LMS) in the subject of electrical lighting installations in the electrical department of class XI TITL SMK N 2 Payakumbuh. The research subjects are students of class XI TITL in the academic year 2022/2023. The purpose of this study was to determine the increase in the effectiveness of learning using a Moodle-based Learning Management System (LMS) in the subject of Electrical Lighting Installation (IPL) at SMK N 2 Payakumbuh. The type of research used is quantitative research with pre-experimental design method using one group pretest-posttest. The data analysis technique used normality test and homogeneity test, classical completeness, t-test, effect size, and normalized gain score. Learning using a moodle-based learning management system (LMS) can be said to be effective, the results of the classical completeness test are effective because they exceed the minimum completeness criteria limit of 85%. The result of the effect size test is 1.62 including the large and effective category. The results of the N-Gain test score of the control class of 0.29 are in the low category but have increased learning outcomes, the experimental class of 0.41 is in the medium category because of the increase in learning outcomes. Based on data analysis, learning using a moodle-based learning management system (LMS) is categorized as effective for learning.